UNLEASHING THE POTENTIAL OF THE INDONESIAN TIMBER LEGALITY ASSURANCE SYSTEM FOR LEGALITY ASSURANCE, PERFORMANCE, AND GLOBAL COMPETITIVENESS - Khaliqi, Muhammad; Wibowo, Rulianda Purnomo; Malau, Leo Rio Ependi; Novianti, Tanti; R. Rambe, Khoiru (Indonesian Journal of Forestry Research, 2025)
Indonesia has responded to the timber certification obligation imposed by importing countries, particularly the European Union, by implementing the Indonesian Timber Legality Assurance System (Sistem Verifikasi Legalitas Kayu-SVLK). This study aimed to evaluate the impact of the SVLK policy on the state of the Indonesian forestry industry and the performance of Indonesian wood goods, mostly plywood, in the international market. Secondary data on Indonesian wood product exports, classified under HS Code 4412, were utilized in this investigation. The analysis revealed that comparative advantage (RCA) analysis was used to assess the competitiveness of Indonesian wood products, while panel data analysis was utilized to assess the impact of the SVLK policy on Indonesian wood export performance. The implementation of SVLK enhanced the value of Indonesian plywood exports; however, the increase was still relatively small compared to other major exporting countries. According to the estimation results, the use of SVLK had a positive impact on the Indonesian plywood trade in the international market. However, Indonesia's ability to increase its market share was still critical so that the Indonesian plywood industry could maximize the potential for expansion in demand for plywood.